Plasticity Modeling & Computation - Borja, Ronaldo I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
There have been many excellent books written on the subject of plastic deformation in solids, but rarely can one find a textbook on this subject. (3z(BPlasticity Modeling & Computation(3y (Bis a textbook written specifically for students who want to learn the theoretical, mathematical, and computational aspects of inelastic deformation in solids. It adopts a simple narrative style that is not mathematically overbearing, and has been written to emulate a professor giving a lecture on this subject inside a classroom. Each section is written to provide a balance between the relevant equations and the explanations behind them. Where relevant, sections end with one or more exercises designed to reinforce the understanding of the (3z(Blecture.(3y (BColor figures enhance the presentation and make the book very pleasant to read. For professors planning to use this textbook for their classes, the contents are sufficient for Parts A and B that can be taught in sequence over a period of two semesters or quarters.s
Motivations and Scope -- One-Dimensional Problem -- J2 Plasticity -- Isotropic Functions -- Finite Deformation -- Cap Models -- Discontinuities -- Crystal Plasticity -- Bifurcation.
Keywords: Engineering; Geography; Materials; Hydraulic engineering; Engineering; Geoengineering, Foundations, Hydraulics; Continuum Mechanics and Mechanics of Materials; Earth Sciences, general